Strategic planning and its relationship with the performance of small and medium-sized enterprises in Gauteng Province - Sandada, Maxwell (My University, 2012)
and medium sized enterprises (SMEs) are the mainstay of economies and societies of many countries around the world. These enterprises are critical to the economy because of the way in which they contribute to the Gross Domestic Product, export revenue generation, innovation, the provision of goods and services thatlarge enterprises depend upon, and the creation of employment opportunities, social stability and improvement of economic welfare. SMEs operate within the economic environment characterised by volatility, dynamism and competitive markets that may seriously threaten their survival. In South Africa, the operating environment for SMEs is constantly changing in the face of a volatile economic environment and a highly competitive market. For SMEs to weather the storm of such volatility and competitive climate, they need to engage in strategic planning processes. While strategic planning research in large organisations has been studied extensively, little attention has been paid to strategic planning of small and medium sized enterprises. Strategic planning has not significantly filtered down to the SME sector. SMEs which practice strategic planning have plans, which are unstructured, less comprehensive and sporadic. There is little evidence of empirical research that has sought to evaluate strategic planning within the sphere of small business research. Therefore, despite the widespread recognition of the importance and significant contributions of SMEs, research on these small businesses remains scarce. There is need for more systematic research aimed at revealing the true nature of strategic planning in SMEs. Despite the contributions of a number of researchers in the field, there is still no universal agreement as to the impact of particular types of planning on SME performance. The study analyses the relationship between strategic planning and the performance of SMEs. It is unique in that rather than using the traditional objective performance measures, subjective measures are used to measure the performance of SMEs. The objective of this study was to establish the relationship between strategic planning and the performance of SMEs measured by perceptual measures of business performance. It also sought to ascertain the relationship between strategic planning and the plans of the business, as well as determining the relationship between business performance and its plans. Another objective was to examine the extent to which SMEs in South Africa have adopted the strategic planning practices. Finally, this study sought to determine if there are differences in strategic planning practices with regard to demographic variables, namely gender, age, and position occupied in the business. A quantitative method was used. Surveys were conducted with 415250 SMEs, which were identified by convenience sampling method. Data from owners/managers of these SMEs was collected using self-administered structured questionnaires. Factor, correlation and regression analyses were conducted and the findings were discussed. The main components of strategic planning include environmental scanning, business mission and vision, formality of strategic planning, employee participation in the strategic planning process, source of information about the environment, strategy implementation incentives, monitoring, evaluation and control, and time horizon of strategic planning. The finding of this study shows that there is a positive causal relationship between strategic planning and the performance of SMEs measured by perceptual measures of business performance. It was also found that there is a mixed relationship between strategic planning and future plans of the SMEs. An additional finding is that business performance has a positive relationship with the plans of the business. The results also indicate that the majority of SMEs practice strategic planning. Finally, the results reveal that the gender, age and occupation of the respondent do not influence the strategic planning practices in SMEs. The only strategic component that depends on the occupation of the respondent is the use of mission and vision statements. Given that today’s business environments for SMEs are characterised by high levels of competition, uncertainty and turbulence, it is recommended that SMEs should adopt more strategic planning practices so that they can make informed decisions. In order to ensure their success and sustainability, SMEs should scan the environment more frequently and seriously than they currently do.
D. Tech. (Logistics, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Strategic planning; Business performance; Small and medium enterprises; Performance measures; 658.0220968; Small business -- Management